THE EFFECT OF PLANTING AND TENDING CROPS METHODS ON SWITCHGRASS BIOMASS PRODUCTIVITY UNDER THE CONDITIONS OF FOREST-STEPPE OF UKRAINE - Гументик M. Я. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
To study and develop effective agronomic methods of planting and tending crops of switchgrass; to set the scientific and reasonable parameters and methods of biomass cultivation. The highest yield of dry biomass and energy output was provided under the row width of 30 cm and planting design involved a marker crop. The factors under study; namely methods of planting and tillage are essential only in the first year of vegetation. The optimal row width; methods of planting and tending switchgrass sowings are found. The article presents the results of studies on the effect of cultivation technology for switchgrass biomass purposed for the production of solid biofuel. Methods of planting; optimal row width and conditions of care during the first year of vegetation are and substantiated.